Pathways to Higher Education: The Role of Learning Culture, Achievement Motivation, and Family Environment in Shaping College Aspirations - Umi Fitria; Enny Kartini; Surahman Surahman (AL-ISHLAH: Jurnal Pendidikan, 2025)
Higher education plays a critical role in enhancing cognitive and non-cognitive skills, supporting workforce competitiveness in the digital era. However, in Indonesia, particularly East Kalimantan, student interest in pursuing tertiary education remains low. This study investigates how learning culture, need for achievement, and family environment influence students' interest in continuing to higher education, with learning motivation examined as a potential mediating variable. A quantitative approach was employed using a survey method. The population comprised 1,562 twelfth-grade students from five public high schools in Samarinda, East Kalimantan. A sample of 410 respondents was selected through proportional random sampling. Data were collected using validated Likert-scale questionnaires and analyzed using Structural Equation Modeling (SEM) via LISREL. Findings revealed that both learning culture and need for achievement have significant direct effects on students' interest in continuing their studies. Family environment, however, did not exhibit a direct influence. Learning motivation was significantly affected by need for achievement and family environment but did not significantly mediate the relationship between learning culture or need for achievement and students' interest in pursuing higher education. It was only a significant mediator in the case of family environment. The study concludes that fostering a strong learning culture and nurturing students’ achievement motivation are key drivers of higher education aspirations. While family environment plays an indirect role, learning motivation is not a universal mediator. These findings offer practical implications for educators and policymakers to strengthen school-based and motivational interventions targeting college readiness and access.